Toxicity of Atorvastatin on Isolated Brain Mitochondria: Neurotoxicity of Atorvastatin - Sanaze Nasohi; Parvaneh Naserzadeh; Nafiseh Rahmanabadi; Banafsheh Saiid; Jalal Pourahmad (Iranian Journal of Pharmaceutical Sciences, 2017)
Background: Although the bio kinetics, metabolism and chemical toxicity of Atorvastatin are well known, until recently little attention was paid to the potential neurotoxic effect of Atorvastatin (Atv). Regarding the concrete evidences indicating Atv may reduce Coenzyme Q10 (CoQ10) levels through blockage of metalonate cycle, the present work aims to determine if Atorvastatin may provide toxic effects on brain mitochondria and whether its supplementation with two lipidicantioxidants, CoQ10 and Vit E may improve such outcomes. Methods: to evaluate mitochondrial toxicity, male NMRI mice were first treated with Atorvastatin(bo; 20 and 60 mg/kg) every other day with or without supplementation with CoQ10 (200 mg/kg) or Vit E (40 u/kg). After a period of 4 weeks, the animals were euthanized and brain cortices were harvested ad subjected to mitochondria isolation procedure. ROS release, mitochondrial membrane potential (MMP) and cytochrome c release were performed to precisely address the probable mitochondrial injury. Findings: Our data showed increased ROS formation, MMP collapse, mitochondrial swelling and cytochrome c release in Atorvastatin treated mice, suggesting that mitochondrial ROS formation and apoptosis signaling are likely involved in Atorvastatin neurotoxicity. Importantly according to the data from animals receiving either CoQ10 or Vit E, supplementation with these lipophilic antioxidants, remarkable reverted the corresponding Atorvastatin mitochondrial toxicity markers. Concusion: Conclusively the present work addresses chronic Atorvastatin toxic effects on brain mitochondria and supports advantages of Vit E or CoQ10 supplementation. Whether such neurotoxic effect is correlated with CoQ10 depletion or if the improving effects of the due supplementation contribute toAtorvastatin receiving patients, needs more investigations.